Influence of Structure, Character of Chemical Bonding and Elastic Properties on the Radiation Stability of Silicates, Phosphates and Metal Oxides Deduced by Computer Simulations - Grechanovsky, A.E.; Brik, A.B.; Ponomarenko, O.M. (Мінералогічний журнал, 2009)
The radiation stability of periclase MgO, rutile TiO2, zircon ZrSiO4, xenotime YPO4, quartz SiO2, cristobalite SiO2, gallium phosphate GaPO4 and fluorapatite Ca10(PO4)6F2 has been studied by computer simulations methods. The number of Frenkel pairs after propagation of the primary knock-оn atom of thorium with a kinetic energy of 10 keV has been characterized by molecular dynamics method. Calculation of chemical bonds covalency degree in studied minerals has been performed using the self-consistent SIESTA method, an implementation of the density functional theory. Calculation of the effective charge of oxygen atoms has been performed using ab initio Hartree-Fock method and B3LYP hybrid functional. It is established that the radiation stability of these minerals depends significantly on the structure topology (the connectivity index, the number of different polyhedra, connected in oxygen positions and the number of nonequivalent positions of oxygen atoms and cations in a structure). Besides, the radiation stability of silicates and metal oxides can be mainly characterized by the effective charge of oxygen atoms. It has been shown, that bulk modulus also influences on radiation stability of silicates with related structures. Радіаційна стійкість мінералів периклазу MgO, рутилу TiO2, циркону ZrSiO4, ксенотиму YPO4, кварцу SiO2, кристобаліту SiO2, фосфату галію GaPO4 та фторапатиту Ca10(PO4)6F2 досліджена за допомогою методів комп’ютерного моделювання. Кількість пар Френкеля, які формуються в структурі мінералу після проходження первинно вибитого атому торію з енергією 10 кеВ, розраховано за допомогою методу молекулярної динаміки. За методом SIESTA (теорія функціонала густини) проведені обчислення ступеня ковалентності хімічних зв’язків для цих мінералів. Обчислення ефективних зарядів атомів кисню проведені з використанням неемпіричного методу Хартрі-Фока та гібридного функціонала B3LYP. Встановлено, що радіаційна стійкість досліджених мінералів значною мірою залежить від топології структури (зв’язність структури, кількість різних поліедрів, що з’єднуються в позиціях атомів кисню, кількість нееквівалентних позицій атомів кисню та катіонів). Окрім того, радіаційна стійкість силікатів та оксидів металів значною мірою залежить від значень ефективних зарядів атомів кисню. Показано, що модуль об’ємної пружності мінералів також є важливим параметром, що впливає на радіаційну стійкість мінералів з однотипними структурами. Радиационная устойчивость таких минералов, как периклаз MgO, рутил TiO2, циркон ZrSiO4, ксенотим YPO4, кварц SiO2, кристобалит SiO2, фосфат галлия GaPO4 и фторапатит Ca10(PO4)6F2 изучена с помощью методов компьютерного моделирования. Количество пар Френкеля, которые формируются в структуре минерала после прохождения первично выбитого атома тория с энергией 10 кэВ, рассчитано с помощью метода молекулярной динамики. По методу SIESTA (теория функционала плотности) проведены вычисления степени ковалентности химических связей для этих веществ. Неэмпирические расчеты методом Хартри-Фока с применением гибридного функционала B3LYP были выполнены для вычисления эффективных зарядов атомов кислорода в минералах. Установлено, что радиационная устойчивость исследованных минералов в значительной степени зависит от топологии структуры (связность структуры, количество различных полиэдров, которые соединяются в позициях атомов кислорода, количество неэквивалентных позиций атомов кислорода и катионов). Кроме того, радиационная устойчивость силикатов и оксидов металлов в значительной степени зависит от значений эффективных зарядов атомов кислорода. Показано, что модуль объемной упругости также служит важным параметром, влияющим на радиационную устойчивость минералов с однотипными структурами.